THE SCIENTIFIC INTERPRETATION OF THE HOLY QURAN: BETWEEN ACCEPTANCE AND REJECTION - A CRITICAL STUDY - Firas Muslm Salim Al-Zubadi (Scholars Digest Publishing, 2025)
This research provides a critical study of the "scientific interpretation of the Holy Quran," examining the debate between two primary trends: the proponent trend, which views it as proof of divine miraculousness and an effective missionary tool in the age of science, and the opposing trend, which warns of its methodological dangers, such as overburdening the text, linking the absolute to the relative, and contradicting the primary purpose of guidance (hidayah). The research concludes that the core issue is not the existence of cosmic allusions in the Quran, but the absence of a disciplined methodology for dealing with them. Therefore, the study proposes a balanced, moderate solution based on five fundamental guidelines: respecting linguistic and contextual meaning, decisively distinguishing between scientific fact and theory, avoiding definitive language, subordinating to the higher purpose of guidance, and considering the Quran a catalyst for science, not a substitute for it. These guidelines aim to preserve the sanctity of the text while remaining open to contemporary contemplation, ensuring the cosmic verses remain a motivator for both science and faith.
Keywords: Scientific Exegesis, Scientific Miracles (I'jaz), Quranic Sciences, Tafsir Methodology, Quran and Science, Interpretation Controls.